2018
DOI: 10.1007/s11596-018-1915-0
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the Study of Lymph Node Metastasis in Early-stage Cervical Cancer

Abstract: Spread into regional lymph node is the major route of metastasis in cervical cancer. Although lymph node status is not involved in the International Federation of Gynecology and Obstetrics staging system of uterine cervical cancer, the presence or absence of lymph node metastasis provides important information for prognosis and treatment. In this review, we have attempted to focus on the incidence and patterns of lymph node metastasis, and the issues surrounding surgical assessment of lymph nodes. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 48 publications
3
37
0
Order By: Relevance
“…In contrast to latestage CC patients, most early-stage (IA2-IIA2) CC patients have a significantly increased survival time after surgery and chemoradiotherapy. However, approximately 10-30% of early-stage patients were found to have pelvic lymph node metastasis (PLNM), and some of the patients eventually experienced adverse outcomes [2]. In earlystage CC, patients with moderately high-risk factors, including large tumor size (> 2 cm), poor differentiation, special pathologic types, deep stromal invasion, lymphovascular space invasion (LVSI), PLNM and parametrial infiltration, usually have relatively shorter survival times [2,3].…”
mentioning
confidence: 99%
“…In contrast to latestage CC patients, most early-stage (IA2-IIA2) CC patients have a significantly increased survival time after surgery and chemoradiotherapy. However, approximately 10-30% of early-stage patients were found to have pelvic lymph node metastasis (PLNM), and some of the patients eventually experienced adverse outcomes [2]. In earlystage CC, patients with moderately high-risk factors, including large tumor size (> 2 cm), poor differentiation, special pathologic types, deep stromal invasion, lymphovascular space invasion (LVSI), PLNM and parametrial infiltration, usually have relatively shorter survival times [2,3].…”
mentioning
confidence: 99%
“…The detection of micrometastasis of lymph nodes requires highly specific biomarkers, such as cytokeratin, SCC and HPV. However, IHC or cytokeratin are considered less specific (3)(4)(5)(6). Dürst et al (13) demonstrated that HPV16-E6-E7-mRNA was more sensitive and specific than cytokeratin-(CK)19-mRNA for the detection of disseminated tumor cells in SLNs.…”
Section: Discussionmentioning
confidence: 99%
“…Lentz et al (3) used immunohistochemistry (IHC) to assess 3,106 lymph nodes from 132 patients with pathologically negative lymph nodes, and reported that micrometastases can be found in 15% patients with early stage cervical cancer who were considered as lymph node negative by conventional histologic analysis. This is due to the failure of traditional pathological methods to diagnose the micro-metastasis of lymph nodes (4), and the fact that detection of micro-metastasis of lymph nodes requires highly specific biomarkers, such as cytokeratin, squamous cell carcinoma antigen (SCC) and human papilloma virus (HPV) (5). However, IHC or cytokeratin are considered less specific (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Although complete uniform pelvic lymphadenectomy is the routine procedure, the total number of pelvic LNs (PLNs) harvested varies among patients. Lymphatic dissemination to the regional LNs has been suggested as the main route of metastasis in cervical cancer [5]. Therefore, complete removal of PLNs is essential to improve survival, as it may increase the likelihood of detecting occult metastatic lesions [6].…”
Section: Clinical Features That Affect the Number Of Pelvic Lymph Nodmentioning
confidence: 99%